Parents of healthy children assign lower quality of life measure to scenarios labeled as cancer than to identical scenarios not labeled as cancer - Brenna M. McElderry; Emily L. Mueller; Abigail Garcia; Aaron E. Carroll; William E. Bennett Jr (BMC Psychology, 2019)
Abstract Background While it is commonly understood that a cancer diagnosis evokes feelings of fear, the effect of labeling a child’s illness as “cancer” remains unstudied. We hypothesized that lower health utility scores would be assigned to disease states labeled as cancer compared to identical disease states without the mention of cancer. Methods In this randomized study, caregivers of healthy children were asked to assign health utility values to different scenarios written as improving, stable, or worsening. Participants from general pediatric clinics at Eskenazi Health were randomly assigned to either the scenarios labeled as “cancer” or “a serious illness”. Participants then rated the scenarios using the Standard Gamble, with laddering of health utilities between 0 (a painless death) and 1 (perfect health). We also gathered subject demographics and assessed the subject’s numeracy. Results We approached 319 subjects and 167 completed the study. Overall median health utilities of “cancer” scenarios were lower than “serious illness” scenarios (0.61 vs. 0.72, p = 0.018). Multivariate regression (with an outcome of having a utility above the 75th percentile) showed no significant effects by race, ethnicity, numeracy, or income level. “Cancer” scenarios remained significantly lower after adjustment for confounders using logistic regression, but only for the more serious scenarios (OR 0.92, p = 0.048). Conclusions On average, caregivers with healthy children were shown to take more risk with their treatment options and view their child as having a worse quality of life when they knew the disease was cancer. Awareness of this bias is important when discussing treatments with families, particularly when a risk of cancer is present.